Ethnic and sex differences in serum levels of cartilage oligomeric matrix protein : the Johnston County Osteoarthritis Project - Jordan, Joanne M; Luta, Gheorghe; Stabler, Thomas; Renner, Jordan B; Dragomir, Anca D; Vilím, Vladimír; Hochberg, Marc C; Helmick, Charles G; Kraus, Virginia, B (Arthritis and rheumatism, 2003)
OBJECTIVE: Previous descriptions of potential biomarkers of osteoarthritis (OA) have been limited to Caucasians. In the present study, we examined associations between serum levels of cartilage oligomeric matrix protein (COMP) and ethnicity (African American or Caucasian) and sex in the Johnston County Osteoarthritis Project, a population-based study of OA in rural North Carolina. METHODS: All African Americans and a randomly selected sample of Caucasians who had available sera and either no radiographic evidence of knee or hip OA according to the Kellgren/Lawrence (K/L) system (K/L grade 0) or radiographic evidence of knee OA (K/L grade 2 or higher) were included. Serum COMP levels were quantified by sandwich enzyme-linked immunosorbent assay, using monoclonal antibodies 16-F12 and 17-C10. Linear regression models were used to assess relationships between serum levels of natural log-transformed COMP (ln COMP) and ethnicity and sex, controlling for age, height, body mass index (BMI), radiographic OA, and the presence of other symptomatic joints. Radiographic OA was defined in separate models as the presence, severity, and laterality of radiographic knee OA, the co-occurrence of radiographic knee and hip OA, and the number of knees and hips with radiographic OA. RESULTS: The 769 subjects in the study sample had a mean +/- SD age of 62 +/- 10.3 years. Levels of ln COMP were associated with age, BMI, and all definitions of radiographic OA (P = 0.0001), and varied by ethnicity and sex. In adjusted models, ln COMP was higher in African American women than in Caucasian women (P = 0.003) and higher in Caucasian men than Caucasian women (P = 0.0001). There were no statistically significant differences in serum ln COMP levels between African American men and women. CONCLUSION: Serum COMP levels vary by ethnicity and sex. These factors should be considered in the derivation of standards using this, and possibly other, potential biomarkers of OA.
Keywords: glykoproteiny; Extracellular Matrix Proteins; Female; černoši nebo Afroameričané; etnicita; biologické markery; Ethnicity; Biomarkers; Black or African American; ženské pohlaví; Knee Joint; lidé; kloubní chrupavka; Glycoproteins; Severní Karolína; artróza kolenních kloubů; Cartilage, Articular; Sex Factors; Male; Aged; extracelulární matrix - proteiny; Osteoarthritis, Knee; Rural Health; lidé středního věku; Random Allocation; North Carolina; senioři; mužské pohlaví; White People; kolenní kloub; běloši; Middle Aged; Rural Population; náhodné rozdělení; Humans